Finding God in all things : celebrating Bernard Lonergan, John Courtney Murray, and Karl Rahner - Bosco, Mark; Stagaman, David J., 1935- (Fordham University Press, 2007)
Three of the most influential Catholic theologians of the twentieth century--Bernard Lonergan, John Courtney Murray, and Karl Rahner-- were all born in 1904, at the height of the Church₂s most militant rhetoric against all things modern. In this culture of suspicion, Lonergan, Murray, and Rahner grew in faith to join the Society of Jesus and struggled with the burden of antimodernist policies in their formation. By the time of their mature work in the 1950s and 1960s, they had helped to redefine the critical dialogue between modern thought and contemporary Catholic theology. After the dťente of the Second Vatican Council, they brought Catholic tradition into closer relationship to modern philosophy, history, and politics.